An Analytical Approach On Improvement Of Kitchen Design Performance In Terms Of Psycho-Social User Requirements - Yazıcıoğlu, Deniz Ayşe (Advances in Social Sciences Research Journal, 2014)
A kitchen design with high performance can be achieved only by creating appropriate solutions in line with the requirements of the person(s) who will use the kitchen. User requirements are mainly divided into two groups as physical requirements and psycho-social requirements. One of the psycho-social requirements of users can be considered as aesthetic needs. When we consider aesthetic requirements in the design of the kitchen we see that the most important components are the countertop material and the cabinet door type and the visual harmony between them. The target and objective of this study in this context is to obtain the statistical data revealing which cabinet door type is used in combination with which countertop material in kitchen design and convert the results incident to such statistical data into a meaningful data analysis table that will help the designer to make the right decision in the choice of cabinet door type and the countertop material. The cabinet door types and the countertop materials which will be studied have been defined at the first stage as the methodology of this study within the purview of this defined scope and purpose with the grounds thereof. Subsequently, 1.309 actual kitchen projects have been examined in order to obtain statistical data showing the relationship between the countertop materials and the cabinet door types. In the final stage of the study the mathematical relationship between these statistical data obtained as a result of these examinations have been converted into a meaningful data analysis table.